Nucleosynthesis bounds on a time-varying cosmological 'constant' - Birkel, M; Sarkar, S (1996)
We constrain proposed phenomenological models for a vacuum energy which decays with the expansion of the universe from considerations of standard big bang nucleosynthesis. Several such models which attempt to solve the cosmological age problem are disfavored or even ruled out.